The Timing of Application and Inclusion of a Surfactant Are Important for Absorption and Translocation of Foliar Phosphoric Acid by Wheat Leaves - Peirce, Courtney A. E.; McBeath, Therese M.; Priest, Craig; McLaughlin, Michael J. (Frontiers in Plant Science, 2019)
Foliar applied phosphorus has the potential to provide a more tactical approach to phosphorus (P) fertilisation that could enhance P use efficiency if effective. The aims of this study were to investigate the influence of adjuvant choice and application timing of foliar applied phosphoric acid on leaf wettability, foliar uptake, translocation and grain yield of wheat plants. We measured the contact angles of water and fertilisers on wheat leaves, and the uptake, translocation and wheat yield response to isotopically-labelled phosphoric acid in combination with five different adjuvants when foliar-applied to wheat at either early tillering or flag leaf emergence. There was high foliar uptake of phosphoric acid in combination with all adjuvants that contained a surfactant but only one treatment resulted in a 12% increase in grain yield and two treatments resulted in a decrease in grain yield. Despite the wettability of all foliar fertilisers being markedly different, foliar uptake was similar for all treatments that contained a surfactant. The translocation of phosphorus from foliar sources was higher when applied at a later growth stage than when applied at tillering despite the leaf surface properties that affect wettability being similar across all leaves at both growth stages. Both the timing of foliar application and the inclusion of a surfactant in the formulation are important for absorption and translocation of phosphoric acid by wheat leaves, however high foliar uptake and translocation will not always translate to a yield increase.